Libraries and Accessibility: Istanbul Public Libraries Case - Gül Yücel (Iconarp International Journal of Architecture and Planning, 2016)
In the study; the assessment of accessibility has been conducted in Istanbul public libraries within the scope of public area. Public libraries commonly serve with its user of more than 20 million in total, spread to the general of Turkey, having more than one thousand branches in the centrums and having more than one million registered members. The building principles and standards covering the subjects such as the selection of place, historical and architectural specification of the region, distance to the centre of population and design in a way that the disabled people could benefit from the library services fully have been determined with regulations in the construction of new libraries. There are works for the existent libraries such as access for the disabled, fire safety precautions etc. within the scope of the related standards. Easy access by everyone is prioritized in the public libraries having a significant role in life-long learning. The purpose of the study is to develop solution suggestions for the accessibility problems in the public libraries. The study based on the eye inspection and assessments carried out within the scope of accessibility in the public libraries subsidiary to Istanbul Culture and Tourism Provincial Directorate Library and Publications Department within the provincial borders of Istanbul. The arrangements such as reading halls, study areas, book shelves etc. have been examined within the frame of accessible building standards. Building entrances, ramps and staircases, horizontal and vertical circulation of building etc. have been taken into consideration within the scope of accessible building standards. The subjects such as the reading and studying areas and book shelf arrangements for the library have been assessed within the scope of specific buildings. There are a total of 34 public libraries subsidiary to Istanbul Culture and Tourism Provincial Directorate on condition that 20 ea. of them are in the European Side.